Pengaruh Pembelajaran Berbasis Inkuiri terhadap Keterampilan Berpikir Kritis Siswa dalam Pembelajaran IPA (SMP-SMA): Meta-Analysis - Sang Nyoman Putra Darma; I Wayan Redhana; I Nyoman Tika (Jurnal Penelitian Pendidikan IPA, 2025)
Critical thinking skills are crucial 21st-century skills. However, students' critical thinking skills are still considered low in several studies. Science learning is closely related to this ability. One learning model believed to effectively improve critical thinking skills is the inquiry-based learning model. This study is a meta-analysis study that aims to examine and determine the effect of the inquiry learning model on improving secondary school students' critical thinking skills in science learning as a whole. Article searches were conducted using PoP on Google Scholar and obtained 11 final articles for analysis. The analysis process used Comprehensive Meta-Analysis (CMA) with the Hedges formula. The results of this study indicate that the fixed-effects model has an effect size of 1.07 (std. error 0.08), while the random-effects model has an effect size of 1.16 (std. error 0.37). This means that inquiry learning has a significant effect on improving critical thinking skills despite study variations. These results are not easily influenced by the possibility of publication bias.